Panacis Quinquefolii Radix: A Review of the Botany, Phytochemistry, Quality Control, Pharmacology, Toxicology and Industrial Applications Research Progress - Yang, Liu; Hou, Ajiao; Zhang, Jiaxu; Wang, Song; Man, Wenjing; Yu, Huan; Zheng, Senwang; Wang, Xuejiao; Liu, Songtao; Jiang, Hai (Frontiers in Pharmacology, 2020)
On January 2, 2020, The National Health Commission and the State Administration for Market Regulation listed Panacis Quinquefolii Radix (PQR) as a medicinal and food homologous product. PQR is the dry root of Panax quinquefolium L., which has the functions of replenishing qi and nourishing Yin, clearing heat and producing body fluid. It is often used for qi deficiency and Yin deficiency, heat exhaustion, asthma and phlegm, dry mouth and pharynx. PQR is sweet, slightly bitter and cool in nature, and enter the heart, lung and kidney meridian exerts the remedial and hygienical effect. At present, active components such as saponins, flavonoids, fatty acids, polyalkynes, volatile oils and other nutrients such as amino acids, carbohydrates, vitamins and trace elements have been isolated from PQR. Modern pharmacological studies have shown that PQR has the effects of hypoglycemic, antihypertensive, anti fatigue, anti-oxidation, anti-tumor, immunomodulatory, neuroprotective and so on. In addition, PQR is recognized as a health care product to strengthen the body and dispel diseases. It is not only the raw material of Traditional Chinese medicine preparations, but also the treasure of dietary therapy and herbal cuisine. This study not only reviewed the botany, phytochemistry and pharmacology of PQR, but also summarized its quality control, toxicity and industrial applications for the first time. This paper not only summarizes the development status of PQR, but also analyzes the shortcomings of the current research on PQR, and puts forward the corresponding solutions, in order to provide reference for future scholars to study PQR.